The Mediating Role of Trust in the Influence of Customer Experience on Repurchase Intention of Emina Local Cosmetic Products in Denpasar City - I Gusti Agung Diandra Prabandari; Tjokorda Gde Raka Sukawati (International Journal of Economics, Management and Accounting, 2025)
In recent years, the beauty industry has gained significant traction and become deeply embedded in public awareness, especially regarding skincare routines involving cosmetic products. Among the notable local cosmetic brands in Indonesia is Emina, which stands out for its youthful concept and lightweight formulations—ideal for entry-level users. This study seeks to explore the mediating role of trust in the relationship between customer experience and repurchase intention for Emina’s products in Denpasar City. Utilizing a non-probability sampling technique, specifically purposive sampling, data were obtained through surveys distributed to 120 qualified respondents. The analysis was conducted using path analysis, complemented by the Sobel test and the Variance Accounted For (VAF) approach. Findings reveal that customer experience significantly and positively affects both trust and repurchase intention. Moreover, trust itself has a significant positive impact on repurchase intention and acts as a mediating variable between customer experience and repurchase intention. Theoretically, this research reinforces prior findings in the field, while practically, it offers strategic insights for Emina’s management to improve consumer experiences and foster trust—ultimately boosting repeat purchase behavior.